A Low-cost model of breast biopsy for the training of surgical residents during COVID-19 pandemic. (January 2022) - Jana, Sinjan; Yadav, Sanjay Kumar; Sharma, Dhananjaya; Agarwal, Pawan
We describe a low-cost simulation model for teaching core needle biopsy to surgical trainees in Low- and Middle-income countries (LMICs). Pre-session and post-session surveys showed that correct core sampling (ability to hit the beetroot) after training was 91.4% compared to 75.7% before demonstration and improved adequacy (68.5% before v. 85.7% after). This low-cost model using locally available products is designed to simulate a palpable breast lump and can easily be incorporated into surgical training in LMICs, where a palpable breast lump is the commonest presentation of breast cancer.